Do Stock Prices Fully Reflect the Implications of Special Items for Future Earnings? - Burgstahler, David; Jiambalvo, James; Shevlin, Terry (Journal of Accounting Research, 2002)
Previous research (Rendleman, Jones, and Latane [1987]; Freeman and Tse [1989]; Bernard and Thomas [1990]; and Ball and Bartov [1996]) indicates that security prices do not fully reflect predictable elements of the relation between current and future quarterly earnings. We investigate whether this finding also holds for the special items component of earnings. Given that special items are prominent in financial analysis and are assumed to have relatively straightforward implications for future earnings (special items are assumed to be largely transitory), one might expect that prices would fully impound the implications of special items for future earnings. Based on the “two‐equation” approach used in Ball and Bartov [1996] and other studies (e.g., Abarbanell and Bernard [1992]; Sloan [1996]; Rangan and Sloan [1998]; and Soffer and Lys [1999]), we find that while prices reflect relatively more of the effects of special items compared to other earnings components, we still reject the null hypothesis that prices fully impound the implications of special items for future earnings. The “two‐equation” approach assesses the consistency of coefficients in a pair of prediction and pricing equations, and thus depends on an assumed functional form. However, a less structured abnormal returns methodology like that used in Bernard and Thomas [1990] also supports the conclusion that the implications of special items are not fully impounded in prices. Specifically, a trading strategy based only on the sign of special items earns small but statistically significant abnormal returns during a 3‐day window four quarters subsequent to the original announcement of special items.